A finite-difference solution of boron/epoxy composite plate with an internal hole subjected to uniform tension/displacements using displacement potential approach - Deb Nath, S. K. (2013)
Finite-difference technique is extended to obtain the stress as well as the displacement components with the deformed shape of a boron/epoxy orthotropic composite plate with an internal hole subjected to uniform tension (case 1)/displacements (case 2) at its two opposite ends. Critical regions are identified by the detailed discussions of the elastic field of the plate problem for both of the cases. Effects of fiber orientation and sizes of the hole on the elastic field of the plate for case 2 are discussed. Boundary condition effects on the elastic field of the plate for case 2 are also investigated. To check the reliability, appropriateness, and soundness of the present approach, firstly the tangential stress component, σϕ along the circular cavity of the plate for case 1 obtained by the finite difference method is compared with that of the classical theory of anisotropic elasticity and secondly the different stress components at the section, y/b=0 and 0.5 of the plate of orthotropic composite materials for case 2 obtained by the finite difference method based on displacement potential approach are compared with those of Finite element predictions by the commercially available ANSYS Finite element software.